1984
DOI: 10.1002/nag.1610080103
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐layer element for interfaces and joints

Abstract: SUMMARYThe idea of using a thin solid element, called a thin-layer element, in soil-structure interaction and rock joints is proposed. A special constitutive model is used and various deformation modes such as no slip, slip, debonding and rebonding are incorporated. The shear stiffness is found from special laboratory tests and the normal stiffness is assumed to be composed of participation of the thin-layer element and the adjoining solid elements. A parametric study shows that the thickness of the thin-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(200 citation statements)
references
References 2 publications
2
171
0
2
Order By: Relevance
“…The fault in rock mass is larger and fewer and can be simulated with the joint element such as Goodman element [19] or Desai element [20]. While obviously different from it, the joint belongs to the third-and fourth-class structural face, which is small, many and nonpersistent, and it cannot be calculated one by one.…”
Section: A Damage Constitutive Model For Rock Mass With Macroscopic Fmentioning
confidence: 99%
“…The fault in rock mass is larger and fewer and can be simulated with the joint element such as Goodman element [19] or Desai element [20]. While obviously different from it, the joint belongs to the third-and fourth-class structural face, which is small, many and nonpersistent, and it cannot be calculated one by one.…”
Section: A Damage Constitutive Model For Rock Mass With Macroscopic Fmentioning
confidence: 99%
“…They are normal hexa-or pentahedral elements in which the length or width to thickness ratio can be up to 1000:1 without causing numerical problems during the calculation [13]. They are implemented to describe the local (joint) dissipation in structures and it has been shown that the simulated damping correlates better with the experimental results than traditional damping modeling methods [1].…”
Section: Modelling Of Materials and Joint Dampingmentioning
confidence: 99%
“…Various possible modes of deformation must be taken into account, including the stick and slip modes, for which normal stress remains compressive, as well as the debonding and rebonding modes, for which normal stress can reach zero. Models for the pipesoil interface describe limiting cases such as perfect adhesion [Selvadurai and Pang 1988], elastic and inelastic springs for both transversal and longitudinal behavior [Zhou and Murray 1993], and continuum interface elements as in the pioneer works [Katona 1983;Desai et al 1984]. More realistic continuum contact models including both normal and longitudinal contact forces models can be generically framed as optimization models, by which the contact constraints are introduced in the general equations of motion through a Lagrangian multiplier formulation and solved through mathematical programming algorithms.…”
Section: Nelly Piedad Rubio Deane Roehl and Celso Romanelmentioning
confidence: 99%